Optimization of high voltage electrodes for 765 kv bus post insulators. (October 2021) - Raja Nayak, M.; Radhika, G.; Devulal, B.; Deepak Reddy, P.; Suresh, G.
Abstract: The designing of the high voltage electrodes such as grading rings, corona rings, and bus conductors for the station bus post insulators at extra and ultra-high voltage levels pays more attention. Improper design dimensions of high voltage electrodes engenders enhancement of electric field stresses and uneven potential distribution across the insulator which results in the catastrophic performance of station bus post insulators. The comprehensive research on appropriate electrode dimensions compared to existing electrode dimensions alters socio-economical benefits to the consumers as well as the design engineers. Practically it is a tedious process to obtain the optimized high voltage electrode design dimensions and their positions in the field. Therefore, a numerical method-based simulation study is adopted to estimate the electric field stress of the high voltage bus post insulator: resulting data may be subsequently used to verify and if necessary to optimize the design of grading rings and bus conductors. This paper presents the variation of the electric field stress and potential distribution at different grading ring and corona ring sizes of the 765 kV bus post insulator. The effect of variation of grading ring diameter and overall diameter at various positions in the field are investigated and compared. From the simulation data carried out, the optimized design dimension setup of the grading ring and corona ring diameters of the 765 kV bus post insulators are suggested. Also, the simulation data tested and compared with the actual grading ring and corona ring dimensions followed by one of the manufacturing industry.